A comparative study of two SOFC based cogeneration systems fed by municipal solid waste by means of either the gasifier or digester. (1st November 2016) - Yari, Mortaza; Mehr, Ali Saberi; Mahmoudi, Seyed Mohammad Seyed; Santarelli, Massimo
Abstract: Two new cogeneration systems (producing power and heating) based on solid oxide fuel cell fed by either the syngas or biogas are proposed. The performance of systems is analyzed and compared with one another from the thermodynamic and economic viewpoints. Applying the conservation of mass and energy as well as the exergy and cost balance equations for each system component and using the engineering equation solver software, the systems are modeled. Through a parametric study, effects of some key variables such as the current density and the stack temperature difference on the systems' performance are investigated. It is found that for power generation, digester based solid oxide fuel cell shows better performance (with a first law efficiency of 40.14% vs 20.31%); however, considering the combined power and heating system, the total efficiency is obtained 51.05% and 58.75% for digester and gasifier based systems, respectively. In addition, it is found that the digester based SOFC is more cost-efficient and has 54% less unit product cost compared to that of the gasifier based system. Highlights: Two new plants based on syngas/biogas fed solid oxide fuel cell are proposed. First law efficiency of syngas fed system is found to be 58.75%. Biogas fed solid oxide fuel cell found to be superior from the economic viewpoint. For syngas fed system, gasifier has the most exergy destruction contribution.